Kewenangan Mahkamah Konstitusi Mengadili Perselisihan Hasil Pemilukada - Sudrajat, Hendra (Jurnal Konstitusi, 2010)
This letters have a purpose to know and analyze authority basic of Constitution Lawcourt of Republic of Indonesia to judging the dispute from the results of district leader and district proxy leader election, and then transferring background about the authority to judging the dispute from the Results of District Leader and District Proxy Leader Election from Appellate Court to Constitution Lawcourt of Republic of Indonesia. So, to analyze basic of Constitution Lawcourt consideration that dispute objects of results of district leader and district proxy leader election don’t have the quantitative character only based on calculation voice results,  but the qualitative character too, namely breaking the rules to general election principles, with the character likes ahead, general, free, secret, then downright and fairly that’s to influence the results of district leader and district proxy leader election. Analyze the election law is used by Constitution Lawcourt of Republic of Indonesia to judging the dispute in Undang-Undang Republik Indonesia No 24 Tahun 2003 about Constitution Lawcourt of Republic of Indonesia or Undang-Undang Republik Indonesia No 12 Tahun 2008 about Undang-Undang Republik Indonesia No 32 Tahun 2008 about District Governance, do not regulate punish the dispute event of district leader and district proxy leader election results.Result of letters indicate that massive and sistematic breaking is apart of the dispute from the results of district leader and district proxy leader election become legal consideration to sufficient the sense  of  public justice progressively cause from quantitative breaking aspect after candidate of district leader and district proxy leader has  been  elected based on recapitulation and calculation voice where their quantitative   just with assessed breaking collision towards procedural and substantive justice both as siniquanom. Though attempt to accommodate overall of democracy aspects from sections and process district leader and district proxy leader election must be main essential to determine and set the results of recapitulation and calculation voice in district leader and district proxy leader election.As letters recommendation, needed regulation product ownself to regulate about mechanism of district leader and district proxy leader election where has been regulated in Undang-Undang Pemerintahan Daerah for all this time, so that affirmation that the district leader and district proxy leader election into the general election  become  less  be clear. By conducting the ownself regulation, hence mechanism of district leader and district proxy leader election will be more clear, especially to overcome and solution the dispute from the results of district leader and district proxy leader  election.